Indonesian Language Learning Based on Children's Songs to Improve Speaking Skills of Elementary School Students - Aprinawati, Iis; Pebriana, Putri Hana (Lembaga Penelitian Dan Publikasi Ilmiah (LPPI) Yayasan Almahmudi Bin Dahlan, 2024)
This study examines the impact of song-based learning on the speaking skills of elementary school students in Indonesia. Speaking skills are a crucial aspect of effective communication and are an essential component of Indonesian language learning at the elementary level. However, many students face difficulties in expressing their ideas verbally due to a lack of self-confidence and limited opportunities for practicing speaking in a supportive environment. This study aims to explore how the integration of children’s songs in the learning process can improve students' speaking abilities.The research method used is an experimental design with a pretest-posttest control group design, comparing the experimental group, which received song-based learning, with the control group, which followed conventional learning. The results showed that the experimental group made significant improvements in all speaking indicators, including pronunciation, intonation, fluency, vocabulary, and sentence structure. These improvements indicate that children's songs not only help enhance speaking fluency but also increase students' motivation and engagement in the learning process. Song-based learning provides students with opportunities to practice speaking repeatedly, helping them internalize language structures, improve pronunciation, and express themselves confidently. Additionally, children's songs also contribute to the development of emotional intelligence and social skills. This study suggests that song-based learning should be more widely implemented in elementary schools across Indonesia to improve students' speaking abilities while creating a more interactive and enjoyable learning environment. Keywords:Song-based learning, speaking skills, elementary school students, pronunciation, fluency, motivation, student engagement.